Adolescents exposed to discrimination: are they more prone to excessive internet use - Bitto Urbanova, Laura; Holubcikova, Jana; Madarasova Geckova, Andrea; van Dijk, Jitse P; Reijneveld, Sijmen A (BMC pediatrics, 2020)
BACKGROUND: The Internet may serve as a suitable environment for discriminated adolescents as they may consider the online space as the place where they have possibility to build social ties they are missing in their offline life or manage their self-presentation. Therefore, our aim was to explore the association between different types of discrimination by peers (because of gender, physical appearance, culture/skin color/language, unfavorable family situation) and excessive Internet use (EIU), and whether gender moderates this association. METHODS: We used data from a representative sample of 6,462 Slovak adolescents (mean age: 13.00, 49.6% boys) from the HBSC study conducted in 2018. Data were collected through online self-reported questionnaires. We assessed the association between various types of discrimination by peers and EIU using linear regression, and the role of gender as potential moderator. RESULTS: Discrimination because of physical appearance was most prevalent (18.0%). Adolescents exposed to discrimination by peers reported higher levels of EIU. We found an interaction of gender on the association of discrimination because unfavorable family situation with EIU. Boys who experienced this type of discrimination were at higher risk of EIU compared to girls. CONCLUSION: Discriminated adolescents are more likely to use the Internet excessively, with some associations being stronger for boys than for girls. Prevention strategies focused on raising adolescent awareness of the risks and benefits of the Internet should target discriminated adolescents, especially boys, as they seem to be the vulnerable group.
Keywords: průzkumy a dotazníky; Female; Internet Use; ženské pohlaví; Peer Group; Surveys and Questionnaires; Adolescent Behavior; Adolescent; Slovakia; lidé; vyrovnaná skupina; používání internetu; Male; mladiství; Internet; Slovenská republika; mužské pohlaví; internet; chování mladistvých; Humans